2022
DOI: 10.1007/s11910-022-01179-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Impact of Infection and Inflammation on Stroke Risk and Outcomes

Abstract: Purpose of the Review Inflammation is a key component in the pathogenesis of cerebrovascular diseases. In the past few years, the role of systemic infection and gut dysbiosis in modulating inflammation and stroke risk has been increasingly acknowledged. In this review, we synthesize contemporary literature on the effects of infection and inflammation on stroke risk and outcomes, with a focus on periodontal disease, COVID-19 infection, and gut dysbiosis. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In turn, this promotes a vascular low-grade inflammatory response, leading to the progression of atherosclerosis [ 25 ]. Hence, inflammation is a common mechanism linking traditional and emerging CV risk factors to the development of atherosclerosis, leading to CAD, large artery thrombotic stroke, and cerebral aneurysms [ 1 , 26 , 27 , 28 , 29 ]. All phases of atherosclerosis, from retention of atherogenic lipoproteins within the arterial wall, to plaque development and rupture, involve a complex network, including innate and adaptive immune systems, bone marrow, and spleen, which modulate the pro-inflammatory and anti-inflammatory activities of protein mediators, such as cytokines, and immune cells such as leukocytes, macrophages, and lymphocytes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this promotes a vascular low-grade inflammatory response, leading to the progression of atherosclerosis [ 25 ]. Hence, inflammation is a common mechanism linking traditional and emerging CV risk factors to the development of atherosclerosis, leading to CAD, large artery thrombotic stroke, and cerebral aneurysms [ 1 , 26 , 27 , 28 , 29 ]. All phases of atherosclerosis, from retention of atherogenic lipoproteins within the arterial wall, to plaque development and rupture, involve a complex network, including innate and adaptive immune systems, bone marrow, and spleen, which modulate the pro-inflammatory and anti-inflammatory activities of protein mediators, such as cytokines, and immune cells such as leukocytes, macrophages, and lymphocytes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review summarizes the current knowledge about the role of inflammation and the immune system in the development of atherosclerosis, the progression to stable and vulnerable plaque, the relationship between the central nervous system and arterial inflammatory response, the role of ageing in promoting atherosclerosis beyond a prolonged exposure to the traditional risk factors, and new therapeutic opportunities targeting inflammation to reduce the CVD burden. Although most studies refer to CAD, the relationship between inflammation and atherosclerosis in coronary and cerebral arteries is based on the same mechanisms [ 1 , 27 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition to conventional vascular risk factors, such as hypertension, diabetes, long-term smoking and drinking and hyperlipidaemia, recent studies have found that inflammation is closely connected to cerebral infarction. [20][21][22] In clinical terms, tuberculosis is a common chronic inflammatory disease. Although tuberculosis meningitis comprises 1% of the incident cases of tuberculosis, it remains the most serious form of extrapulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, periodontal treatment can reduce serum total cholesterol, low-density lipoprotein, oxidized low-density lipoprotein, and other lipid levels. The role of these mechanisms in preventing the occurrence and progression of atrial fibrillation remains unclear [30][31][32] .…”
Section: Conjecture About Related Underlying Mechanismsmentioning
confidence: 99%